THE SYNERGISTIC EFFECT OF AR INTERACTIVITY AND PERSONALIZATION ON CONSUMER BEHAVIOR IN E-COMMERCE - Kembau, Agung Stefanus; Laimeheriwa , Imagodeo Bideyesa; Kumaat, Arief Perdana (FEB Universitas Sam Ratulangi Manado, 2024)
This study investigates the impact of Augmented Reality (AR) interactivity on digital behavioral intentions in e-commerce, with AR personalization serving as a mediating variable. Focusing on 148 Generation Z respondents in Indonesia who have used AR Try-On features, the research employs a quantitative approach using an online questionnaire and data analysis via Structural Equation Modeling (SEM) through SmartPLS. The results demonstrate that AR interactivity significantly enhances digital behavioral intentions, while personalization amplifies this effect by tailoring AR experiences to individual preferences. The combined influence of interactivity and personalization is particularly strong, highlighting the importance of integrating these elements into e-commerce strategies. These findings are especially relevant in the context of Indonesia's rapidly growing e-commerce market, where consumer preferences are diverse and technology adoption is high. The study provides actionable insights for e-commerce businesses aiming to optimize their digital marketing strategies by leveraging AR technologies to drive higher engagement, satisfaction, and conversion rates. Limitations of the study include the sample size and reliance on self-reported data, suggesting avenues for future research with larger and more diverse samples. Keywords: Augmented Reality (AR), Digital Behavioral Intentions, Interactivity, Personalization, E-commerce, Gen Z, Digital Marketing